Agir en fonction de ce qui n'est pas là - Patrick Mayen (Université de Provence, 2017)
John Dewey's philosophy can be read as a therapy whose potential leads us to see what we have in front of us and but do not see, but also to see what we can do when we do not know anymore how to do it. In terms of education and training, ideas that prevent us from seeing and prevent teachers and trainers from perceiving what they have in front of them are not lacking. In this article, we examine some of John Dewey's ideas that are meaningful in training situations and activities and lead actors to find ways of thinking and acting that will enable them to do what they did manage to do before.